The Political Strategy of Suparyo, SH (Incumbent) In Winning The Village Head Elections In 2016 And 2022 - Nurtiawan Gultom (Journal of Law, Politic and Humanities, 2024)
The Village Head Election is a manifestation of the implementation of Regional Autonomy in accordance with Law No. 23 of 2014 concerning Regional Government, which operates at the smallest level of government, namely the village. In every Village Head Election, there are multiple candidates competing for the highest authority in the village. Therefore, strategy is essential in winning a political contest. The purpose of the research is to understand the political strategies of Suparyo, SH (the incumbent) in winning the village head elections in 2016 and 2022, as well as to identify which strategies were most effective for Suparyo, SH in the Bandar Khalipah village head elections in 2016 and 2022. The research method used in this study is qualitative research. The theory used in this research is the theory of Henry Mintzberg and James Brian, which includes strategy as a plan, ploy, pattern, position, and perspective. From the research findings, the strong influence of the incumbent, the success of the ongoing programs, and the strategies that have been arranged with the success team have successfully led Mr. Suparyo SH to victory in two terms. Approaching three groups of society, namely the general public, fanatics, and beginners, is the main point of focus.